Preparation and swelling properties of homopolymeric alginic acid fractions/poly(N‐isopropyl acrylamide) graft copolymers. Issue 32 (11th May 2015) - Martínez‐Gómez, Fabián; Encinas, María V.; Matsuhiro, Betty; Pavez, Jorge
ABSTRACT Graft copolymers of crosslinked poly(N‐isopropyl acrylamide) (PNIPAAm) and homopolyguluronic acid (GG) and homopolymannuronic acid (MM) fractions of alginic acid were synthesized. MM and GG block fractions were obtained by partial acid hydrolysis of the alkaline extract from the brown seaweed Macrocystis pyrifera. The conjugation of these block fractions with the synthetic polymer was achieved by amidation with crosslinked PNIPAAm functionalized with an amino group at the end of the polymer chain. The structure of conjugates was determined by Fourier transform infrared and NMR spectroscopy. Atomic force microscopy of the graft copolymer GG‐g‐PNIPAAm showed a regular porous pattern, whereas the MM‐g‐PNIPAAm graft copolymer showed a regular netlike structure. Aqueous solutions of the synthesized graft copolymers afforded hydrogels by stirring with 0.1M CaCl2. The hydrogels showed a well‐defined stimulus–response to temperature and pH. The swelling, thermal, and pH characterizations demonstrated the superior properties of the GG‐g‐PNIPAAm hydrogel over the MM‐g‐PNIPAAm hydrogel. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42398.